Duke-Elder's Views on Prognosis, Prophylaxis, and Treatment of Myopia: Way Ahead of His Time. (2nd January 2016) - Polling, Jan Roelof; Verhoeven, Virginie J.M.; Tideman, J. Willem L.; Klaver, Caroline C.W.
ABSTRACT: Sir Stewart Duke-Elder was probably the most influential ophthalmologist of the 20th century. One of his visionary pieces of work was his writing on myopia in the second edition of The Practice of Refraction, published in 1935. Many of his insights are now, 80 years later, supported by scientific proof. In terms of prognosis of myopia, he stated that this largely depended on the age of the patient. We now have epidemiologic evidence that age of onset is strongly related to final refractive error, and that high myopia carries a high risk of blindness. With respect to prophylaxis, he claimed that accessory risk factors were excessive near work, bad ocular hygiene, and physical debility in the early years of growth: "The régime of modern schools imposes far too much application to books upon young children at an age when they require all their available vitality for physical growth and development." He recommended open-air pursuits and avoidance of indoor activities, in particular for children with a hereditary tendency toward myopia. Current investigations indeed point to a crucial role for near work, although not all findings are consistent. The most established factor that is protective from myopia is outdoor exposure, more likely due to intense exposure to light rather than to "open-air." Ocular hygiene and physical activity have not been confirmed as protective factors, but Duke-Elder's views on gene–environment interactions are truly insightful. Concerning treatment, he suggested that adequate correction by glasses, intake of vitamin D, and restriction of education in "myope classes" could halt progression of myopia. Optical correction is considered helpful nowadays, but sound statistical evidence has only been provided for orthokeratology. High vitamin D serum levels are indeed related to low refractive error, but it is not yet clear whether high dietary intake is beneficial. Restriction of education does not meet current moral standards, but in China, "myopia classrooms" in the form of large cubes of windows, admitting lots of light, have been built. In this report, we highlight Duke-Elder's insights into the causes and clinical care of myopia, and discuss their merit for ophthalmic care today.